Empathy in the School Exploring Suffering Among Teachers - Thomas, Nissy James (South Sulawesi Education Development, 2025)
This case study examined the impact of empathy on emotional suffering and job satisfaction among school teachers. The study surveyed 30 teachers from a private school in Abu Dhabi using a structured quantitative questionnaire. Descriptive and inferential statistics were used to examine patterns in empathy levels as well as emotional fatigue and job satisfaction with comparisons, based on gender and years of teaching experience. The findings showed that higher levels of empathy were linked with greater emotional fatigue particularly among teachers in emotionally demanding roles. Moreover female educators and those with fewer years of teaching experience reported greater emotional strain. Although empathy enriched relationships, it also contributed to emotional exhaustion highlighting the need for structured emotional support and resilience training.